1999
DOI: 10.1128/aac.43.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Generation of Oxygen Partially Explains Electrical Enhancement of Tobramycin Efficacy against Pseudomonas aeruginosa Biofilm

Abstract: The role of electrolysis products, including protons, hydroxyl ions, reactive oxygen intermediates, oxygen, hydrogen, and heat, in mediating electrical enhancement of killing of Pseudomonas aeruginosa biofilms by tobramycin (the bioelectric effect) was investigated. The log reduction in biofilm viable cell numbers compared to the numbers for the untreated positive control effected by antibiotic increased from 2.88 in the absence of electric current to 5.58 in the presence of electric current. No enhancement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…Ultrasound [51][52][53] and electric fields [54][55][56] have been used to enhance the efficacy of antibiotics in killing biofilm bacteria in sterilization processes. Ultrasonic irradiation enhanced the killing of P. aeruginosa in biofilms by gentamicin by nearly two orders of magnitude [51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound [51][52][53] and electric fields [54][55][56] have been used to enhance the efficacy of antibiotics in killing biofilm bacteria in sterilization processes. Ultrasonic irradiation enhanced the killing of P. aeruginosa in biofilms by gentamicin by nearly two orders of magnitude [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…O'Leary et al [53] have shown that statistically significant bactericidal effects of ultrasonic irradiation upon pure cultures of the periodontal pathogens P. gingivalis and A. actinomycetemcomitans were due to the incidental temperature increase [53]. On the other hand, small direct current electric fields achieved a 6-to 8-log increase in killing after 24 hours of exposure to the direct current using biofilms of P. aeruginosa [54][55][56]. An electric current enhanced the efficacy of gentamicin against the oral microorganism Streptococcus gordonii in an in vitro biofilm model [57].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mechanisms proposed in the literature are (1) electrochemical generation of oxidants on the surface (Costerton et al 1994), (2) contraction or expansion of biofilm structure (Stoodley et al 1997), (3) electrolytic generation of oxygen during water electrolysis (Stewart et al 1999), and (4) electrostatic and electrophoretic repulsive forces (Hong et al 2008). However, none of these mechanisms is widely accepted because of conflicting results in the literature and the impossibility of comparing the different electrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…With application of direct current electric fields between 1.5 and 20 Vcm -2 (current densities of about 15 10 -6 to 2.1 10 -3 Acm -2 ), the concentrations of antibiotics needed to be effective against biofilm bacteria fell from approximately 5000 times to 4 times greater than those necessary for planktonic bacteria in the absence of electricity [82]. Electrolytic generation of oxygen may be partly responsible for this bioelectric effect, at least with the aminoglycoside antibiotic tobramycin against P. aeruginosa biofilm [83]. Enhanced antibiotic activity has also been shown using pulsed electromagnetic fields (PEMF).…”
Section: Electrical Enhancement Of Antimicrobial Activitymentioning
confidence: 96%